An investigation of the behavioral, normative, and control beliefs of college students who do not intend to possess a credit card: a reasoned action approach - Cupples, William Sam (Kansas State University, 2016)
The purpose of this dissertation was to examine the factors associated with students’ intentions to not possess and use a credit card. This dissertation focused on exploring a sample of undergraduate college students who do not possess a credit card. There is little known research on this group of students. The dissertation was directed by the following over-arching research question: The goal of this study was to explore college students’ beliefs about not possessing a credit card using the Theory of Reasoned Action (TRA). The research questions for this dissertation were: (a) How is personality (i.e., individual background factor) of undergraduate college students associated with their behavioral, normative, and control beliefs to not possess a credit card, (b) How are education level, age, gender, income level, religiosity, marital status, and ethnicity (i.e., social background factors) of undergraduate college students associated with their behavioral, normative, and control beliefs to not possess a credit card, and (c) How is financial knowledge (i.e., information background factor) of undergraduate college students associated with their behavioral, normative, and control beliefs to not possess a credit card. This study collected primary data. A pilot study was conducted to set the stage for the data collection of the current study. The data analysis methodology for this study consisted of the following four methods: (a) Factor Analysis, (b) Correlation Analysis, (c) MANOVA, and (d) Discriminant Function Analysis. Factor analysis identified questions were used to develop scales to measure the dependent variables. Strong reliability estimates were obtained, ranging from .84 to .94. The MANOVA test identified seven hypotheses with statistically significant results < .05. Control beliefs were significantly associated with personality. The five personality types, extraversion, agreeableness, conscientiousness, neuroticism, and openness, were all found to be significantly associated with either behavioral beliefs, control beliefs, or injunctive normative beliefs. Extraversion, agreeableness, conscientiousness, and neuroticism were all found to be associated with control beliefs. While agreeableness was also associated with injunctive normative beliefs, openness was found to be associated with behavioral beliefs. Financial knowledge was found to be associated with control beliefs. Discriminant function analysis was performed as a confirmatory test of the results from the MANOVA test, and supported the results of the MANOVA for six of the hypotheses.
Keywords: Individual & Family Studies; Theory of Planned Behavior; No intention of having a credit card; Behavioral sciences; Consumer behavior; Personal financial planning